Electrodeposition of Crystalline HgTe from a Non-Aqueous Plating Bath. Issue 16 (1st January 2018) - Kissling, Gabriela P.; Aziz, Mohsin; Lodge, Andrew W.; Zhang, Wenjian; Alibouri, Mehrdad; Huang, Ruomeng; Hector, Andrew L.; Reid, Gillian; de Groot, Cornelis H.; Beanland, Richard; Bartlett, Philip N.; Smith, David C.
Abstract : This paper presents a method for the electrodeposition of stoichiometric, crystalline HgTe, which provides advantages over conventional HgTe preparation techniques, such as physical and chemical vapor deposition, in a number of ways; e.g. fast deposition rates (2 μm/hr) and the ability to reliably produce stoichiometric or near-stoichiometric material. The HgTe is prepared in a dichloromethane based plating bath using [N n Bu4 ]2 [TeCl6 ] and [N n Bu4 ]2 [HgCl4 ] as the precursors for Te and Hg, respectively. The paper details the electrochemical behavior of the plating bath and its components, together with a detailed characterization of the morphology, crystallinity and composition of the prepared HgTe.